Exigência de lisina digestível para panga (Pangasius hypophthalmus) com base no crescimento, deposição corporal, hematologia e variáveis metabólicas - BATISTA, Vanessa Ferreira (2024)
Lysine (Lys) is the essential amino acid found in the highest proportion in fish carcasses, with an almost exclusive function for the deposition of body protein and is generally limiting in diets of plant origin. The objective was to estimate the digestible Lys requirement for Panga (3.20 ± 0.05 g). Six diets were formulated, with different levels of total Lis, being 11.00, 14.00, 17.00, 20.00, 23.00, 26.00 g kg-1 (corresponding to 9.14, 12.54, 15.64, 18.94, 22.44, 24.12 g kg-1 of digestible Lys) offered until apparent satiety, in a Completely Randomized Design, for 60 days. Referring to zootechnical performance, body deposition, hematology and metabolic variables. According to quadratic regression (p<0.05), final weight, weight gain, relative weight gain, feed conversion rate and specific growth rate obtained the best results at estimated levels of 16.75; 16.76; 16.78; 17.17 and 16.60 g kg-1 digestible Lys respectively. Crude protein, ash and fat contents were affected quadratically (p<0.05) up to levels of 18.59; 19.50 and 16.30 g kg-1 digestible Lys, respectively. Protein, ash and body fat depositions, and nitrogen retention efficiency, increased quadratically (p<0.05) up to a concentration of 17.93; 16.94; 17.43 and 18.33 g kg-1 digestible Lys, respectively. The activity of the liver enzyme Aspartate Aminotransferase, quadratically impaired (p<0.05) at the estimated level of 17.18 g kg-1 of digestible Lys. The values of liver glycogen and total proteins varied quadratically to estimated levels of 18.33 and 18.73 g kg-1 digestible Lis, respectively. Dietary Lys levels also quadratically (p<0.05) affected erythrocyte count and corpuscular hemoglobin concentration up to estimated levels of 18.46 and 16.18 g kg-1 digestible Lys, respectively. Blood plasma biochemical parameters were not affected (p>0.05). It is concluded that the digestible Lys requirement for Panga is 17.93 g kg-1 of digestible Lys, corresponding to 5.98% of the dietary CP.